Study of a repair technique in carbonated blended mortars: Electrochemical re-alkalization (2016)
The present article studies the influence of two pozzolanic additions, metakaolin (MK) and silica fume (SF), and the water/binder ratio (w/b) on the electrochemical re-alkalization (ER) of reinforced mortars as a technique to prevent reinforcement corrosion in carbonated concrete. Mixtures with a 10% (by weight) addition as a replacement for cement at w/b ratios of 0.45 and 0.65 were prepared. Test specimens were exposed to carbonation in a chamber under controlled conditions (1% CO2, 65%RH, and 25°C), until reaching two levels of carbonation (50% and 100%). ER was applied for a period of 15 days using sodium carbonate as the electrolyte and a current density of 1 A/m2. From the evaluated additions, MK is highlighted, which generated a resistance increase of 53.51% relative to that of the reference mixture and contributes to improvements of durability properties. Regarding the ER technique, the specimens with greater w/b ratios and partial carbonation were more effective.